P2.056 Prevalence of Neisseria Gonorrhoeae Specimens Containing Por A Pseudogene Deletion Among Gonococcal Resistance to Antimicrobials Surveillance Programme (GRASP)Specimens at the Health Protection Agency. (13th July 2013) - Toby, M; Ison, C; Saunders, P
Abstract : Background: There has been an emergence of Neisseria gonorrhoeae strains which although phenotypically are indistinguishable from N. gonorrhoeae, vary in their genotype and require heightened surveillance. Isolates of N. gonorrhoeae were identified in Scotland, Australia and Sweden which lacked sequences in the porA pseudogene (PAP) and consequently gave false negative results in the PAP real-time polymerase chain reaction (RT-PCR) for N. gonorrhoeae . In 2011 two PAP negative isolates were found in England. We sought to determine the prevalence of PAP negative isolates amongst those received through the national surveillance programme, GRASP. Method: A screening protocol was devised which entailed using initial PAP testing followed by repeat PAP and confirmatory opa RT-PCR testing. Lysates prepared from isolates received for GRASP during 2011 were used. Any lysate with an initial PAP negative result was serially diluted to check for inhibition, then repeated on the original lysates and if still negative confirmed on a freshly prepared isolate direct from the archived isolate. Results: Of 156 GRASP lysates tested 146/156 (94%) were PAP positive, 10/156 (6%) samples were initially found to be PAP negative. On repeat testing however only a single isolate remained PAP negative when repeat PAP testing was performed on samples prepared from fresh culture. Conclusion: A single PAP negative specimen has been identified to date within GRASP, which potentially is carrying the menginococcal PorA. However confirmation by meningococcal PCR will be necessary.